MOBILE USAGE, SHOPPING BEHAVIOR AND STUDY HABIT AS CONTRIBUTING FACTORS OF DEPRESSION, ANXIETY AND STRESS AMONG UNIVERSITY STUDENTS - Nadzirah Mawi; Asma Perveen; Hazalizah Hamzah, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study aims to investigate the effect of certain factors of behavioral aspects on negative emotional states among university students. The behavioral aspects that are selected as independent variables in this study are mobile usage, buying behaviour and study habits. On the other hand, the negative emotional states that are discussed in this study is depression, anxiety and stress. Students (N=377) from Universiti Pendidikan Sultan Idris were selected using stratified sampling and purposive sampling as respondents in this study. Correlation analysis were carried out to briefly inform the reader the relationship between independent variable and dependent variable, and also the interrelationship among them. There is a small effect indicated by correlation coefficient between mobile usage and depression, and between mobile usage and anxiety. On the other hand, there is a moderate relationship between mobile usage and stress. As for shopping behaviour variable, the results indicated it correlates more with anxiety, followed by stress lastly with depression. Last but not least, there is a significant negative relationship between study habit and all dependent variables. As for among independent variables themselves, the results indicated that there is a significant correlation between that mobile usage with shopping behaviour, but not with study habit. Same goes to between shopping behaviour and study habit. On the contrary, among dependent variables themselves, the results indicated that there is a significant high correlation between all of them. Multiple regression analysis is conducted by using SPSS software after testing the assumptions. The results of the regression indicated that the model was a significant predictor of depression, anxiety and stress. Study habit is a significant contributing factor to reduce depression among university students. Besides that, shopping behavior and study habit are significant contributing factor to anxiety among university students. On the contrary, mobile usage and study habit are significant contributing factor to stress among university students.